Interrumpir la interculturalidad - Vich, Víctor (2024)
This article reviews the debate around the category of interculturality to highlight its theoretical achievements and its current relevance in public policy. However, it also attempts to show its limits, contradictions and aporias. Beyond asking what interculturality refers to, it reviews how it is used and what effects it has in the spaces where it is implemented. The ideas arise from a permanent observation of different projects, although this is not ethnographic research. In this case, it has been of interest to place the theoretical discussion in the foreground.